Investigation of cross-section geometry and sediment transport capacity in non-cohesive alluvial channels - Hadadin, Nidal Adeeb, author; Watson, Chester C., advisor; Julien, Pierre, committee member; Grigg, Neil S., committee member; Vlachos, Evan, committee member (Colorado State University. Libraries, 2003)
The assumption of a channel width, which is frequently based on a regime equation (Copeland et al., 2001), is required in the design of an alluvial channel shape. However, the application of regime equations outside the range of the empirical data sets from which each equation was developed presents a potential risk that may be unacceptable to the design engineer. Most empirical equations were developed for streams transporting less than 500 ppm of sediment (Garde and Ranga Raju, 1985; Watson et ah, 1999). This research develops a procedure for channel shape design that does not require the use of regime equations, and can be used for a broader range of sediment transport concentration. In this research, the effect of the width/depth ratio (w/d) on sediment transport was demonstrated based on statistical analysis on a set of hydraulic variables, using regression analyses. Three sediment transport equations were modified to include a width/depth ratio. Two sediment transport relationships were developed, one for natural channels, and another for the laboratory flumes. The results show that the width/depth ratio has an important role in prediction of sediment transport, but the role is less important than the role of flow velocity, channel slope, and grain size. The trends from five sediment transport relationships show that the sediment transport decreases as w/d increases for natural channels and sediment transport increases as w/d increases for flumes. A computational procedure was developed to examine the relationship between maximum sediment transport and the channel width/depth ratio. An investigation of the relationship between width/depth ratio and several different sediment transport relationships was then conducted. Examination of Engelund and Hansen (1967), Yang (1973) for sand and gravel, and Shen and Hung (1971) equations showed that the maximum sediment concentration occurred at a width/depth ratio value of 2, which almost never occurs in natural alluvial channel systems. A comparison was made between Duboys (1879) and Meyer-Peter and Muller (1948) with regime charts (USACE, 1994) for the 2-year recurrence interval discharge using a maximum sediment transport method. It was found that both of the sediment transport equations could be used for prediction of the regime (US ACE, 1994) width/depth ratio. A range of width/depth ratio at maximum sediment transport was found to be 18 to 35 for channels with gravel. For Demonstration Erosion Control (DEC) channels using regression Channel Evolution Model (CEM) relationships, the range of width/depth ratio was found to be 9.8 to 15.1 for channels with sand and top widths <50 m. A new method for stable channel design was developed by modifying the Copeland (1999) procedure. This new method uses Brownlie's (1981) sediment transport equation for sand and was compared with those of other investigators. Based on the results, it was found that this method could be used to design the cross-section geometry for non-cohesive alluvial channels with low and high sediment concentration.
Keywords: civil engineering